2019
DOI: 10.21203/rs.2.14736/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and genotyping of Toxoplasma gondii in stray cats in Mashhad area, Iran.

Abstract: Background: Cats as a definitive host have an important role in the epidemiology of toxoplasmosis in humans and animals. The aim of the study was to determine the frequency of Toxoplasma gondii infection and isolate and identify the genotypes of T. gondii in stray cats in Mashhad suburb. Methods: From April 2016 to August 2017, 175 fecal samples from stray cats and 31 brain samples from cats killed in driving accidents were collected. The fecal samples were examined by fecal flotation technique and T. gondii -… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…This result was consistent with the detection of type-I T. gondii GRA6 in domestic cats in South Thailand [46] and Okinawa, Japan [47]. Other studies have considered type-II T. gondii as the predominant genotype for feline definitive hosts in China [44] and stray cats in Iran [48]. Furthermore, isolates of T. gondii types I and II have been detected via GRA6 marker PCR-RFLPs in oocyst-contaminated soil samples from North Iran [49].…”
Section: Discussionsupporting
confidence: 84%
“…This result was consistent with the detection of type-I T. gondii GRA6 in domestic cats in South Thailand [46] and Okinawa, Japan [47]. Other studies have considered type-II T. gondii as the predominant genotype for feline definitive hosts in China [44] and stray cats in Iran [48]. Furthermore, isolates of T. gondii types I and II have been detected via GRA6 marker PCR-RFLPs in oocyst-contaminated soil samples from North Iran [49].…”
Section: Discussionsupporting
confidence: 84%
“…For instance, in two studies of China serologic evidence of infection was found in 12.71 % of sheep and 20.3 % of goats [ 24,25].Additionally, in an effort by Dubey et al to estimate seropositivity of 234 goats in USA, it was shown 53.4% of goats were positive [13].It is well known that discrepancies in overall seropositivity results for toxoplasmosis in animals may be attributed to kind of used serological test, sample size, ecological status, management and hygienic standards and other factors.Generally, MAT was selected as a rst choice method to evaluate seropositivity of Toxoplasma in animals, whereas in several studies molecular methods were used to determine the rate of toxoplasmosis in animals [19].In this regard, our molecular results via B1 gene shows 58.7 % and 53.3 % of studied sheep and goats were infected with T.gondii and this is in agreement with the nding of 56.66 % and 44.16 % for sheep and goats in Kerman province respectively [26].In line with our nding in Iran,Aziziet alshows that 38 % of studied sheep in ChaharmahalvaBakhtiary province were infected with Toxoplasma; As well assimilar results were taken in the Fars province in the investigation of 56 sheep and 22 goats tissue samples witch total molecular prevalence of Toxoplasma was 33.3 % [19,27].Our molecular prevalence data are comparable with other worldwide reports; for example in Tunisia, it has been proved that 33.3 % and 32.5 % of B1 gene Nested PCR tests were positive for ewes and goats respectively [28].Routinely, genotyping as a crucial determinant for pathogenesis and virulence of Toxoplasma was performed in recent studies. It has been reported that there is a correlation between of T.gondii genotype and clinical symptoms and pathogenesis pro le of parasite [29,30].Besides, it is veri ed that genotype I known as acutely virulent; whereasgenotype II and III are signi cantly less virulent that can establish latent toxoplasmosis [31].Due to speci c polymorphisms of GRA6 marker, it was selected in our study to genotyping of isolated T.gondii and at the next step PCR-RFLP test viaMseІ endonuclease was performed to discriminate between types I, II, and III [32].Nested-PCR of GRA6 gene for 10 tissue samples (7 sheep and 3 goats) was positive and RFLP technique approved all of them cluster into genotype І. These results are in agreement with two previous surveys of different parts of Iran [33,34].It is proven that predominant genotype in animal especially ruminants in Iran is genotype II; Whereas prior European investigation demonstrated the most predominant genotype belongs to type III [35].In our study, variables analysis in sheep and goats showed that infection rate of toxoplasmosis increased with age.…”
Section: Discussionmentioning
confidence: 99%